PENGARUH UKURAN PERUSAHAAN, STRUKTUR MODAL, DAN LIKUIDITAS TERHADAP PROFITABILITAS - Amellia, Radhitta Diena; Puspitaningtyas, Zarah; Karyadi, Hari (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya, 2024)
The covid-19 pandemic has increased people's need for health products, making healthcare sector companies more attractive. However, Indonesia is still dependent on imports of raw materials for medicines, which causes import costs to increase and suppress company profits. To improve performance and profits, healthcare sector companies must compete and improve operational efficiency. This study aims to determine the effect of company size, capital structure, and liquidity on profitability in healthcare sector companies listed on the Indonesia Stock Exchange in 2018-2022. This study uses secondary data in the form of financial reports and annual reports from 17 healthcare sector companies listed on the Indonesia Stock Exchange in 2018-2022 as research samples. The analysis method used is multiple linear regression analysis with three independent variables, namely company size (natural logarithm of total assets), capital structure (debt to equity ratio), and liquidity (current ratio). The dependent variable in this study is profitability (return on asset). The results showed that company size has no partial effect on profitability, capital structure has no partial effect on profitability, and liquidity has a partial effect on profitability.